Developing Bus Rapid Transit’s Schedule using Max Load Method (Trans Metro Bandung Corridor 2 Case Study) - Dionisius Aldwin; Fran Setiawan; Loren Pratiwi (Jurnal Ilmiah Teknik Industri, 2021)
Congestion is one of problems that must be solved by the Government of Bandung City. One of the projects are improving the public transport sector. Trans Metro Bandung (TMB) is one of public transport at Bandung. People’s interest to use TMB is very low. This happens because TMB does not have a reliable bus schedule. The focus of this study is to build a TMB’s corridor 2 schedule with headway based on the current passenger condition. The headway is determined using the max load method. This study will compare the current headway target set by TMB with the headway based on the passenger arriving pattern. After that, the schedule which is made from the choosen headway will be simulated. This study shows that the current headway set by Trans Metro Bandung management is better. Simulation shows that schedule can reduce passenger average waiting time quite significant.